A highly sensitive signal-on biosensor for microRNA 142-3p based on the quenching of Ru(bpy)32+–TPA electrochemiluminescence by carbon dots and duplex specific nuclease-assisted target recycling amplification. Issue 49 (15th May 2020) - Yang, Jiao; Xia, Qian; Guo, Longhua; Luo, Fang; Dong, Yongqiang; Qiu, Bin; Lin, Zhenyu
Abstract : CDs have been used to quench the ECL of Ru(bpy)3 2+ –TPA for the first time and a sensitive biosensor was developed. Abstract : Carbon dots (CDs) have been used to quench the electrochemiluminescence (ECL) of a Ru(bpy)3 2+ –tripropylamine (TPA) system for the first time. In addition, this phenomenon has been coupled with duplex specific nuclease-assisted target recycling amplification to develop a highly sensitive ECL biosensor for microRNA.